Business Intelligence framework to support Chronic Liver Disease Treatment - Khedr, Ayman (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Business Intelligence (BI) framework designs the architecture of business intelligence information system which uses expert systems and Artificial Intelligence technology to support clinical decision and draw the strategy against chronic liver disease in Egypt. It makes integrated diagnostic and medical advice bases on the collected patient’s information, providing reference for the clinical medical officers. This paper aims to support decision function and in particular utilization of historical data laboratory and outcome data processed through artificial intelligence tools. The combination of historical data and predictive tools provides valuable information in the hands of physicians as they develop a course of treatment for a patient